An assessment of temporal variability in mast seeding of North American Pinaceae. (6th December 2021) - LaMontagne, Jalene M.; Redmond, Miranda D.; Wion, Andreas P.; Greene, David F.
Abstract : Our overall objective is to synthesize mast-seeding data on North American Pinaceae to detect characteristic features of reproduction (i.e. development cycle length, serotiny, dispersal agents), and test for patterns in temporal variation based on weather variables. We use a large dataset ( n = 286 time series; mean length = 18.9 years) on crop sizes in four conifer genera ( Abies, Picea, Pinus, Tsuga ) collected between 1960 and 2014. Temporal variability in mast seeding (CVp) for 2 year genera ( Abies, Picea, Tsuga ) was higher than for Pinus (3 year), and serotinous species had lower CVp than non-serotinous species; there were no relationships of CVp with elevation or latitude. There was no difference in family-wide CVp across four tree regions of North America. Across all genera, July temperature differences between bud initiation and the prior year (Δ T ) was more strongly associated with reproduction than absolute temperature. Both CVp and Δ T remained steady over time, while absolute temperature increased by 0.09°C per decade. Our use of the Δ T model included a modification for Pinus, which initiates cone primordia 2 years before seedfall, as opposed to 1 year. These findings have implications for how mast-seeding patterns may change with future increases in temperature, and the adaptive benefits of mast seeding. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.